2021
DOI: 10.1017/s1479262121000241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phenotypic diversity of apricot (Prunus armeniacaL.) accessions from Jammu and Kashmir, India

Abstract: Apricot (Prunus armeniaca L.) is a world-wide highly appreciated fruit, with its attractive colour, soft texture and typical flavour. In the current investigation, 68 apricot accessions collected from Jammu and Kashmir, India were analysed to determine the measure of variation using 12 qualitative and 16 quantitative traits with an aim to identify superior apricot accessions with excellent fruit quality traits. High phenotypic variability was observed among the studied apricot accessions with significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The considered phenotypic traits resulted polymorphic with at least two different categories each ( Figure 3 and Figure S1 ). In general, a huge variation was observed among the cultivars, mostly concerning the fruit’s quality-related attributes, leaf morphology and some phenological traits, as also reported by other authors [ 25 , 49 , 54 , 55 ]. Among the most variable traits were fruit size, shape and acidity, the skin ground color and hue of the skin over-color, the flesh color and adherence to the stone.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The considered phenotypic traits resulted polymorphic with at least two different categories each ( Figure 3 and Figure S1 ). In general, a huge variation was observed among the cultivars, mostly concerning the fruit’s quality-related attributes, leaf morphology and some phenological traits, as also reported by other authors [ 25 , 49 , 54 , 55 ]. Among the most variable traits were fruit size, shape and acidity, the skin ground color and hue of the skin over-color, the flesh color and adherence to the stone.…”
Section: Resultssupporting
confidence: 71%
“…Several studies have analyzed the morphological and genetic diversity of apricot and peach collections, although few have directly compared these two closely related species. Recent works have underlined the great potential of some apricot accessions to be directly cultivated or employed in breeding programs thanks to their high level of phenotypic [ 25 ] and genetic [ 26 , 27 ] variability. Similarly, some studies about peaches mainly aimed to study the genetic variation among cultivars and to preserve the existing variability [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Germplasm description based on morphological and agronomic characters is of notable prominence for the commencement of crop breeding programmes and documentation of advanced accessions (Pereira-Lorenzo et al ., 2012; Zargar et al ., 2021). Sixty-one buckwheat accessions were studied in the present study based on nine quantitative and eight qualitative traits.…”
Section: Discussionmentioning
confidence: 99%
“…The CVs, which can reflect the variation range of phenotypic traits [28,29], showed that the dispersion degree was highest for the FA among the examined morphological traits of apple germplasm resources. The Shannon-Wiener genetic diversity index can also reflect phenotypic trait diversity [30]. The mean genetic diversity index of the analyzed morphological traits was 0.87, ranging from 0.54 (the FP) to 1.33 (the FOC).…”
Section: Genetic Diversity Associated With the Phenotypic Traits Of A...mentioning
confidence: 99%